THE COMPETITIVENESS OF SLOVAK FOREIGN TRADE IN THE EUROPEAN MARKET - Pavličková, Viera (Economic Annals, 2013)
The paper deals with the competitiveness of the Slovak Republic in its ability to succeed in foreign markets. It provides a complex view of Slovak foreign trade within the European Union using a sectoral classification of products. Several appropriate methods (Constant Market Share Analysis, Revealed Comparative Advantage, Michaely Index, and unit export and import values) are applied to quantify the competitiveness of Slovak foreign trade and to identify the level and trend of its specialisation. The analysis uses the data provided by the Eurostat Comext database for the period 1999-2011. The results confirmed Slovakia as a former transition country to be a fast developing open economy. Its production is competitive in the European market, although mainly with prices. Labour- and capital-intensive commodities, along with the automotive industry, dominate Slovak foreign trade. Technology- and R&D-driven goods have a comparative disadvantage as a consequence of several factors, such as lack of innovation and creativity in the business sphere. A shift towards export of more sophisticated products would be beneficial in supporting long-term sustainable development; however, no significant change in Slovak commodity structure has occurred over the past years.